Catalytic C‐Alkylation of Pyrroles with Primary Alcohols: Hans Fischer's Alkali and a New Method with Iridium P, N, P‐Pincer Complexes. Issue 14 (30th March 2018) - Koller, Sebastian; Blazejak, Max; Hintermann, Lukas
Abstract : Hydrogen‐autotransfer alkylation (HAT or "borrowing‐hydrogen" alkylation) of heteroaromatic compounds has been studied with a range of substrates recently, but pyrroles have been largely absent from such studies. The conditions for HAT alkylations of pyrroles were investigated under a variety of conditions and were found to take place under basic alcoholic conditions (Hans Fischer alkylation) in the absence of transition‐metal catalysts; by means of a heterogeneous Pd/C catalyst in the presence of base; and finally by means of homogeneous transition‐metal catalysis combining a base and iridium pincer complexes generated in situ that have not previously been used in HAT alkylations of heterocycles. Abstract : The alkylation of pyrroles with primary alcohols and alkali base at 220 °C was realized by Hans Fischer one hundred years ago. However, this hydrogen‐autotransfer (borrowing‐hydrogen) alkylation proceeds under much milder conditions in the presence of iridium P, N, P‐pincer complex catalysts.